2018
DOI: 10.1371/journal.pntd.0006220
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous overexpression of an active phosphorylated form of DNA polymerase β under oxidative stress in Trypanosoma cruzi

Abstract: Trypanosoma cruzi is exposed during its life to exogenous and endogenous oxidative stress, leading to damage of several macromolecules such as DNA. There are many DNA repair pathways in the nucleus and mitochondria (kinetoplast), where specific protein complexes detect and eliminate damage to DNA. One group of these proteins is the DNA polymerases. In particular, Tc DNA polymerase β participates in kinetoplast DNA replication and repair. However, the mechanisms which control its expression under oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…In trypanosomatids, Pol β is perhaps one of the most studied TLS polymerases. While only one POLB gene has been described for Leishmania spp (Alonso et al, 2006 ; Khan et al, 2019 ), mainly located at the nucleus, in T. cruzi (de Oliveira Lopes et al, 2008 ; Schamber-reis et al, 2012 ; Rojas et al, 2018 ) and T. brucei (Saxowsky et al, 2003 ), the enzyme is mainly located in mitochondria. Interestingly, in T. brucei , two Pol β variants have been described: Pol β and Pol β-PAK (an Nt domain rich in proline-alanine-lysine, only found in these protozoans).…”
Section: Dna Polymerases Families Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In trypanosomatids, Pol β is perhaps one of the most studied TLS polymerases. While only one POLB gene has been described for Leishmania spp (Alonso et al, 2006 ; Khan et al, 2019 ), mainly located at the nucleus, in T. cruzi (de Oliveira Lopes et al, 2008 ; Schamber-reis et al, 2012 ; Rojas et al, 2018 ) and T. brucei (Saxowsky et al, 2003 ), the enzyme is mainly located in mitochondria. Interestingly, in T. brucei , two Pol β variants have been described: Pol β and Pol β-PAK (an Nt domain rich in proline-alanine-lysine, only found in these protozoans).…”
Section: Dna Polymerases Families Overviewmentioning
confidence: 99%
“…Experimental data remains to be carried out to confirm if they are real homologs. In T. cruzi has been shown that Pol β and Pol β-PAK-like have dRP lyase activity, and moreover Pol β-PAK-like is able to bypass 7,8-dihydro-8-oxoguanine (8-oxoG), strongly suggesting specialized roles in BER and TLS for kDNA oxidative protection and maintenance (de Oliveira Lopes et al, 2008 ; Rojas et al, 2018 ).…”
Section: Dna Polymerases Families Overviewmentioning
confidence: 99%
“…The high form is heavily phosphorylated (H), while the low form is unphosphorylated (L). Interestingly, the high form is more active in in vitro DNA synthesis [ 96 ]. The levels of the phosphorylated active form of the enzyme are higher in H 2 O 2 -treated cells compared with untreated cells, suggesting that this activity is involved in repair of the kinetoplast DNA and perhaps is also responsible of the kinetoplast DNA replication [ 96 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the high form is more active in in vitro DNA synthesis [ 96 ]. The levels of the phosphorylated active form of the enzyme are higher in H 2 O 2 -treated cells compared with untreated cells, suggesting that this activity is involved in repair of the kinetoplast DNA and perhaps is also responsible of the kinetoplast DNA replication [ 96 ]. A mechanistic model to explain the overexpression of Tcpol β is outlined in Figure 3 and it can be observed the different protein families involved in the posttranscriptional expression of the enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation